Implikasi Hukum Terkait Penguasaan Harta Bawaan Ayah oleh Istri Kedua dan Anaknya - Nadya Asriyani Sjahrain; Nur Mohamad Kasim; Dolot Alhasni Bakung (AHKAM, 2025)
The main problem addressed in this study is the unilateral appropriation of a father’s premarital property by his second wife and their child, which ignores the inheritance rights of the children from the first marriage and thereby raises issues of justice and legal certainty within the family inheritance context. This study aims to analyze the implementation of inheritance distribution of the father’s premarital assets to the children from the first marriage from the perspectives of Islamic law and positive law, as well as to examine the legal consequences arising from such unilateral control. The research employs a normative–empirical legal approach that combines a doctrinal analysis of legal literature with an examination of concrete cases in the field through a statutory and qualitative approach. Data were obtained through observation and in-depth interviews with a judge of the Religious Court of Gorontalo City, an official of the North Gorontalo Land Agency (BPN), and the relevant heirs, and were analyzed descriptively and qualitatively using Islamic law and civil law theories. The findings show that, based on the Kompilasi Hukum Islam (KHI) and the Kitab Undang-Undang Hukum Perdata (KUHPerdata), children from the first marriage are legitimate heirs who possess equal rights to their father’s premarital property, without any distinction in birth order. The unilateral appropriation of assets by the second wife is classified as an unlawful act because it contravenes Article 176 of the KHI and Article 852 of the KUHPerdata. The study concludes that such actions render the legitimacy of unilateral control null and void and give rise to an obligation to restore the property to all rightful heirs. The implications of this research underscore the importance of strengthening public legal awareness and optimizing the role of judicial institutions in ensuring the just distribution of inheritance in order to prevent and minimize prolonged family conflicts.